Lessons in Pushkin Studies in the Editorial Practice of A. G. Dostoevskaya - Stepchenkova, Valentina (Neizvestnyj Dostoevskij, 2024)
A. S. Pushkin had a great influence on the development of Russian culture in the 19th century, including book publishing. Pushkin’s motifs and images have repeatedly appeared in the works of F. M. Dostoevsky. The last year of the writer’s life was marked by the triumphant “Pushkin’s Speech,” which turned the overall idea of Russian literature upside down. A. G. Dostoevskaya, who began an active bibliographic and publishing life after the death of her husband, followed the tradition of Pushkin’s publications in it. By the time the Complete Works of F. M. Dostoevsky were published, Pushkin studies had already actively solved textual problems, thereby facilitating subsequent researchers and publishers to work on compiling collections of works and bibliographies of writers. Systematizing her husband’s collected materials, A. G. Dostoevskaya focused on the bibliographic index of Pushkin’s works “Puschkiniana,” compiled by V. I. Mezhov. This is evidenced by the notes she made in her notebooks. The main consultant to the writer’s widow, who for several years had been independently preparing the first bibliography of Dostoevsky for publication, was P. A. Efremov, bibliographer, Pushkin scholar and editor of the Complete Works of A. S. Pushkin. In the poet’s anniversary year of 1899, A. G. Dostoevskaya published Dostoevsky’s Pushkin’s Speech in a separate edition, calling it “Pushkin” and thereby contributing to the celebration of the founder of Russian literature. Pushkin’s work played a significant role not only in Dostoevsky’s biography and literary legacy, but also in the bibliographic and traditional activities of the writer’s wife.